2018
DOI: 10.7717/peerj.5519
|View full text |Cite
|
Sign up to set email alerts
|

Association of burnout with doctor–patient relationship and common stressors among postgraduate trainees and house officers in Lahore—a cross-sectional study

Abstract: IntroductionBurnout is defined as a prolonged state of physical and psychological exhaustion. Doctors, due to the demanding nature of their job, are susceptible to facing burnout, which has far reaching implications on their productivity and motivation. It affects the quality of care they provide to patients, thus eroding the doctor–patient relationship which embodies patient centeredness and autonomy. The study aims at addressing the stressors leading to burnout and its effect on the doctor–patient relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
4
12
3
1
Order By: Relevance
“…The caring dimension obtained a higher score, indicating a greater preference for the socio‐affective side of PCC than for sharing information and power. This result, while corroborated by several studies, 29,31,32,44,45 could depend on the cultural background of professionals or their medical specialty 46,47 . In our sample, s haring subscale items that obtained more physician‐oriented responses were related to the patients’ need for information and searches for themselves.…”
Section: Discussionsupporting
confidence: 88%
“…The caring dimension obtained a higher score, indicating a greater preference for the socio‐affective side of PCC than for sharing information and power. This result, while corroborated by several studies, 29,31,32,44,45 could depend on the cultural background of professionals or their medical specialty 46,47 . In our sample, s haring subscale items that obtained more physician‐oriented responses were related to the patients’ need for information and searches for themselves.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that the effect of gender is compounded by the possible effects of cultural differences as studies have been conducted in different settings (Ishak et al, 2009). The nding in this study that males are more prone to work-related and client-related burnout than their female counterparts contrasts with the ndings of another study (Ahmad et al, 2018) who described that female trainees were more likely to suffer from burnout. Ripp et al (2010) found no signi cant differences in burnout between genders.…”
Section: Discussioncontrasting
confidence: 76%
“…Our burnout rates were lower than French mental healthcare low level burnout (77.5%); higher than the French moderate level burnout (17.8%); and roughly the same as the French high level burnout (4.6%) [51] and consistent with the rates for Spanish physicians and nurses, where the low level burnout rate was 58.8%, the moderate level was 37.5% and the high level was 3.7% [21]. For medical staff in Heilongjiang, the moderate and high level burnout rate was 84.62% and signi cantly higher than Pakistani postgraduate trainees and house o cers' high level burnout rate of 29.8% [52,53] In uencing Factors Of Burnout…”
Section: Discussionsupporting
confidence: 68%